2017
DOI: 10.1016/j.ncrna.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Translational applications of microRNAs in cancer, and therapeutic implications

Abstract: The search for targeted novel therapies for cancer is ongoing. MicroRNAs (miRNAs) display a number of characteristics making them an attractive and realisable option. In this review, we explore these applications, ranging from diagnostics, prognostics, disease surveillance, to being a primary therapy or a tool to sensitise patients to treatment modalities such as chemotherapy and radiotherapy. We take a particular perspective towards miRNAs and their impact on rare cancers. Advancement in the delivery of miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 86 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Emerging evidence suggests that miRNAs can function as tumor suppressors or oncogenes depending on their target mRNAs, thereby markedly affecting the biology of cancer. [19][20][21] Several miRNAs have been identified as being associated with different cancers, including OS, 22,23 and there is evidence that miR-193b acts as a tumor suppressor in various types of cancer. [24][25][26][27][28][29][30] In the present study, we demonstrated that miR-193b expression is lower in OS specimens than in adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that miRNAs can function as tumor suppressors or oncogenes depending on their target mRNAs, thereby markedly affecting the biology of cancer. [19][20][21] Several miRNAs have been identified as being associated with different cancers, including OS, 22,23 and there is evidence that miR-193b acts as a tumor suppressor in various types of cancer. [24][25][26][27][28][29][30] In the present study, we demonstrated that miR-193b expression is lower in OS specimens than in adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have outlined an important role of miRNAs for the prediction of prognosis and outcome in many human cancers (Kwok et al 2017). miRNAs are small endogenous non-coding RNA molecules (18-25 nucleotides) which may repress protein expression.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…In addition, miRNA offers the opportunity to target multiple mRNA targets with a single miRNA in a given pathway. [46] [47] It is important to mention that although miR-based therapeutics have demonstrated great promise for the treatment of different diseases, this is still an evolving field. The main obstacle for clinical application of RNA-based therapeutics is determining how to best deliver the agent to targeted cells.…”
Section: Mir-155-mediated Loss Of Cell Surface Cd47 Promotes the Phagmentioning
confidence: 99%